VD_FINDINFO HC / 2015 / 828 vom 28. September 2015 - VD Tribunal cantonal (2015)
EXPULSION DE LOCATAIRE, BAIL À LOYER, PRINCIPE DE LA BONNE FOI, CAS CLAIR | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 271 al. 1 CO, 271 CO, 257 CPC (CH)